1992
DOI: 10.1001/archsurg.1992.01420020127019
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid Cystic Carcinoma of the Breast

Abstract: Adenoid cystic carcinoma of the breast is a rare neoplasm, with only 140 cases having been reported to date. Data on 123 of these cases are reviewed herein and another case is presented in detail. Several features distinguish this type of breast cancer from more typical histologic types and suggest that it may have a unique tumor behavior. The prognosis appears to be favorable and the incidence of axillary lymph node involvement is lower. Distant metastases are uncommon, but they tend to occur without prior ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 18 publications
3
49
1
Order By: Relevance
“…adenoid cystic carci noma presents as a mass that is occasionally tender to palpation. The tumor is rarely fixed to the overlying skin, nipple, or pectoral muscles [6]. All cases presenting signs of microscopic in vasionshowedeitherill-definedor partiallyill definedmarginson mammograms (Fig.…”
Section: Billroth Coinedthe Term â€Oe¿ Cylindroma― In Hismentioning
confidence: 99%
“…adenoid cystic carci noma presents as a mass that is occasionally tender to palpation. The tumor is rarely fixed to the overlying skin, nipple, or pectoral muscles [6]. All cases presenting signs of microscopic in vasionshowedeitherill-definedor partiallyill definedmarginson mammograms (Fig.…”
Section: Billroth Coinedthe Term â€Oe¿ Cylindroma― In Hismentioning
confidence: 99%
“…Pathological criteria of ACC involves biphasic cellular pattern consists of basaloid myoepithelial cells together with ductal epithelial cells (7). In the presented case, a triple negative phenotype was detected.…”
Section: Case Reportmentioning
confidence: 52%
“…AAC of the breast also showed lower proliferative activity with PR and ER usually negative. Leeming et al (5) reviewed 140 cases and found only one case positive in ER. However, in a different group, which consisted of 14 cases, there were 4 positive in ER and in a separate group of 13, there were 3 positive in PR (6).…”
Section: Discussionmentioning
confidence: 99%
“…Sumpio et al (9) reported 6 cases of local recurrence following simple lumpectomy, out of a total of 8 cases. Leeming et al (5) noted that 9 out of 24 patients suffered from local recurrence following simple lumpectomy, a recurrence rate of 37%. Youk et al (15) described a case of local recurrence following successful treatment by lumpectomy and systemic chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation